2022
DOI: 10.1186/s10194-022-01415-x
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness after initiating fremanezumab treatment in US patients with episodic and chronic migraine or difficult-to-treat migraine

Abstract: Background Fremanezumab, a fully humanized monoclonal antibody (mAb; IgG2Δa) that selectively targets calcitonin gene-related peptide (CGRP), is approved for the preventive treatment of migraine in adults. The efficacy and safety of fremanezumab for migraine prevention have been demonstrated in randomized, double-blind, placebo-controlled trials. Real-world effectiveness data are needed to complement clinical trial data. This study assessed the effectiveness of fremanezumab across different sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 44 publications
(31 reference statements)
3
19
2
2
Order By: Relevance
“…Adverse reactions were also collected from clinical records. A subanalysis was also conducted on the effect of CGRP mAbs in patients with daily headache (no day without headache at baseline), prior use of CGRP mAbs (those receiving second or third types of CGRP mAbs with insufficient response to the first or second types of CGRP mAb treatment) and difficult-to-treat (DTT) migraine (those with MOH or psychiatric comorbidities) (17).…”
Section: Methodsmentioning
confidence: 99%
“…Adverse reactions were also collected from clinical records. A subanalysis was also conducted on the effect of CGRP mAbs in patients with daily headache (no day without headache at baseline), prior use of CGRP mAbs (those receiving second or third types of CGRP mAbs with insufficient response to the first or second types of CGRP mAb treatment) and difficult-to-treat (DTT) migraine (those with MOH or psychiatric comorbidities) (17).…”
Section: Methodsmentioning
confidence: 99%
“…From the real-world aspect, a retrospective, panel-based, online chart review analyzed the effectiveness of fremanezumab among CM patients in the US and demonstrated that the mean reduction from baseline in MMDs at month 6 was 10.1 [ 90 ].…”
Section: Recommended Prophylactic Treatment Options In CMmentioning
confidence: 99%
“…[73,74] A US-based retrospective, panel-based online chart review included 220 patients with AMO, 134 patients with major depression disorder, and 120 patients with generalized anxiety disorder. [73] In that study, reductions from baseline in mean MMD were observed as early as 1 month, with increasing reductions through 6 months in patients with AMO (mean [percent reduction] at 6 months: −10.1 [68.7%]), major depressive disorder (−9.9 [68.3%]), and generalized anxiety disorder (−9.5 [66.4%]). The ≥50% responder rates at 6 months were 78.8%, 81.8%, and 80.0% in the AMO, major depressive disorder, and generalized anxiety disorder subgroups, respectively.…”
Section: Preventive Treatment Options For Migrainementioning
confidence: 99%
“…[71,72,77] Further, there is now limited evidence from real-world studies in patients with AMO, MOH, and psychiatric comorbidities that support the findings of these subgroup analyses, demonstrating the effectiveness of CGRP pathway-targeted mAbs for preventive treatment of migraine in these populations. [65–68,73,74]…”
Section: Treatment Of Migraine With Amo or Psychiatric Comorbidities:...mentioning
confidence: 99%
See 1 more Smart Citation